2021
DOI: 10.1021/jacs.1c04324
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Protein Degradation through Fast Optogenetic Activation and Its Application to the Control of Cell Signaling

Abstract: Development of methodologies for optically triggered protein degradation enables the study of dynamic protein functions, such as those involved in cell signaling, that are difficult to be probed with traditional genetic techniques. Here, we describe the design and implementation of a novel light-controlled peptide degron conferring N-end pathway degradation to its protein target. The degron comprises a photocaged N-terminal amino acid and a lysine-rich, 13-residue linker. By caging the N-terminal residue, we w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…NIH 3T3 cells coexpressing the ERK KTR− mCherry reporter and WT-or K30HCK-PH−EGFP−SOS cat were serum starved for 5 h to block extracellular stimulation of the ERK/mitogen-activated protein kinase (MAPK) signaling cascade. As expected, in the absence of ERK signaling, the reporter was localized in the nucleus (Figure 5C 66,67 matching activation kinetics previously observed upon Phy-PIF optogenetic SOS2 translocation to the cell membrane. 65 The activity level of the reporter in the presence of the decaged construct closely resembled that observed with the WT-PH−EGFP−SOS cat positive control, which induced constitutive ERK signaling activity and sustained cytoplasmic reporter accumulation (Figure 5C(second row),D).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…NIH 3T3 cells coexpressing the ERK KTR− mCherry reporter and WT-or K30HCK-PH−EGFP−SOS cat were serum starved for 5 h to block extracellular stimulation of the ERK/mitogen-activated protein kinase (MAPK) signaling cascade. As expected, in the absence of ERK signaling, the reporter was localized in the nucleus (Figure 5C 66,67 matching activation kinetics previously observed upon Phy-PIF optogenetic SOS2 translocation to the cell membrane. 65 The activity level of the reporter in the presence of the decaged construct closely resembled that observed with the WT-PH−EGFP−SOS cat positive control, which induced constitutive ERK signaling activity and sustained cytoplasmic reporter accumulation (Figure 5C(second row),D).…”
supporting
confidence: 86%
“…Membrane accumulation of the K30HCK-PH–EGFP–SOS cat protein upon light stimulation, as observed by EGFP imaging, resulted in activation of the ERK signaling cascade, inducing complete cytoplasmic accumulation of the reporter within 60 min of irradiation (Figure C­(last row),E). The speed of the reporter response is similar to previous examples of light-induced ERK KTR activation in NIH 3T3 cells, which range from 20 to 60 min for complete accumulation, , matching activation kinetics previously observed upon Phy-PIF optogenetic SOS2 translocation to the cell membrane . The activity level of the reporter in the presence of the decaged construct closely resembled that observed with the WT-PH–EGFP–SOS cat positive control, which induced constitutive ERK signaling activity and sustained cytoplasmic reporter accumulation (Figure C­(second row),D).…”
supporting
confidence: 86%
“…Notably, the proteolytic activities of PROTACs could be precisely controlled by merging them with photo-pharmacological groups, such as azobenzene photo-switchable linkers 44,45 or light-removable caging groups. 46,47 However, the conjugation of functional groups with PROTACs increases the molecular weight to over 1000 Da, which might compromise the oral bioavailability, solubility, and/or pharmacokinetic properties. Additionally, the clinical application of existing light-controllable PROTACs is very limited as they usually require ultraviolet light to turn on its activity, which is poor in tissue penetration and may trigger DNA damage to human skins and tissues.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…Recent studies reported the success of localizing the effects of PROTACs in cancerous cells and tissues by adding them with functional features. For example, conjugating PROTACs with folate or antibody achieves selective degradation of POIs in cancer cells versus noncancerous cells, thus enhancing the therapeutic windows of PROTACs. Notably, the proteolytic activities of PROTACs could be precisely controlled by merging them with photo-pharmacological groups, such as azobenzene photo-switchable linkers , or light-removable caging groups. , However, the conjugation of functional groups with PROTACs increases the molecular weight to over 1000 Da, which might compromise the oral bioavailability, solubility, and/or pharmacokinetic properties. Additionally, the clinical application of existing light-controllable PROTACs is very limited as they usually require ultraviolet light to turn on its activity, which is poor in tissue penetration and may trigger DNA damage to human skins and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this is the first reported use of genetic code expansion for photocaging of an allosteric site. Typically, protein control has been achieved through photocaging of protein–substrate interactions, photocaging of catalytic sites, or photocaging of cofactor binding sites. ,,,,, Here, we have provided an approach in which optical restoration of effector binding facilitates substrate recruitment and phosphatase activity.…”
Section: Discussionmentioning
confidence: 99%